Increasing the Safety Factor of Clay Shale Slopes Using Bored Pile by Limit Equilibrium Method - Simanjuntak, Mario Antoni; Fathki, Redha; Sriyana (Kadiri University, 2025)
The clay shale slopes of the Rukoh Dam Supplementary Structure exhibit high susceptibility to weathering and shear strength reduction, which directly impacts long-term stability. This vulnerability demonstrates the importance of slope reinforcement and the need to consider the fully softened condition that represents the long-term behavior of degraded clay shale material in the field. This study aims to determine the stability of the Rukoh Dam Supplementary Structure’s clay shale slopes with bored pile reinforcement. Soil characteristic data were tested in the Laboratory to obtain shear strength. Evaluations were performed at peak and fully softened conditions using Fellenius and Plaxis LE calculations. The bored pile design was calculated based on the slope stability evaluation results and requirements to achieve a safety factor of 1.5. The results showed that slope stability was significantly reduced when the material was fully softened, with a safety factor of 0.74, thus not meeting long-term service requirements. Increasing the stability to FS 1.5 was achieved using a bored pile system with a diameter of 0.8 m and a total length of about 11 m, which can provide a moment capacity of about 364,818 kNm. These findings indicate that bored pile reinforcement can improve long-term slope stability under clay shale conditions.